Thunks and the lambda-Calculus - Hatcliff, John; Danvy, Olivier (BRICS Report Series, 1996)
Thirty-five years ago, thunks were used to simulate call-by-name under call-by-value in Algol 60. Twenty years ago, Plotkin presented continuation-based simulations of call-by-name under call-by-value and vice versa in the lambda-calculus. We connect all three of these classical simulations by factorizing the continuation-based call-by-name simulation Cn with a thunk-based call-by-name simulation T followed by the continuation-based call-by-value simulation Cv extended to thunks. We show that T actually satisfies all of Plotkin’s correctness criteria for Cn (i.e., his Indifference, Simulation, and Translation theorems). Furthermore, most of the correctness theorems for Cn can now be seen as simple corollaries of the corresponding theorems for Cv and T.